Real and Financial Integration in East Asia - Soyoung Kim; Jong-Wha Lee (Asian Development Bank (ADB), 2008)
We examine the real and financial integration of East Asian economies, comparing the degree of real versus financial integration, the degree of global versus regional integration, and the extent of integration before versus after the 1997/98 financial crisis in East Asian economies. We analyze price and quantity measures of integration such as the size of intra- and inter-regional trade, cross-border financial assets, correlation of stock returns, and interest rate differentials. In addition, we adopt a panel VAR approach of investigating cross-country output inter-dependence and consumption relation in order to infer the macroeconomic consequences of real and financial integration on East Asian economies. The empirical investigations suggest that (i) using the quantity measure there is a significant increase in real integration within East Asia; (ii) real-side integration based on output linkage increased substantially after the Asian crisis, both regionally and globally; (iii) although quantity and price measures showed some degree of increased financial integration after the crisis, the cross-country consumption relation did not change much; (iv) the degree of regional financial integration within Asia is far smaller than the degree of global financial integration, based on the consumption-based measure; and (v) financial integration lags real integration, especially for regional integration within Asia.
hdl:11540/1771
Keywords: F15; F36; F41; 330; Trade and financial integration; global and regional integration; risk sharing; East Asia